Motivasi dan Kendala Investasi di Batam - Muhammad Zaenuddin (Politeknik Negeri Batam, 2012)
The research is aimed to identify the motivation and obstacles of investment as well as to analyze factors influencing investment decisions in the industrial estates in Batam. 25 companies and the management from 8 industrial estates are selected as respondents using convenience sampling. The result of this research indicates that the major motivation of choosing investment location in Batam are labor factor, cost, licensing administration, the importance of tax incentive, the importance of FTZ in Batam, contiguity to Singapore and market factors. Other reasons are the availability of skilled and woman labors, electricity, export and access to regional/global markets, rental cost, and also port facility. Investment constraint is administrative affair and licensing and also uncertainty of the implementation of FTZ in Batam. While according to industrial area management, investment constraints that require to be corrected are bureaucracy problems, high cost economics, taxation, customs, immigration, labor, and land problems.